Self-Healing Dynamic Hydrogel Microparticles with Structural Color for Wound Management - Wang, Li; Ding, Xiaoya; Fan, Lu; Filppula, Anne M.; Li, Qinyu; Zhang, Hongbo; Zhao, Yuanjin; Shang, Luoran (Nano-Micro Letters, 2024)
Chronic diabetic wounds confront a significant medical challenge because of increasing prevalence and difficult-healing circumstances. It is vital to develop multifunctional hydrogel dressings, with well-designed morphology and structure to enhance flexibility and effectiveness in wound management. To achieve these, we propose a self-healing hydrogel dressing based on structural color microspheres for wound management. The microsphere comprised a photothermal-responsive inverse opal framework, which was constructed by hyaluronic acid methacryloyl, silk fibroin methacryloyl and black phosphorus quantum dots (BPQDs), and was further re-filled with a dynamic hydrogel. The dynamic hydrogel filler was formed by Knoevenagel condensation reaction between cyanoacetate and benzaldehyde-functionalized dextran (DEX-CA and DEX-BA). Notably, the composite microspheres can be applied arbitrarily, and they can adhere together upon near-infrared irradiation by leveraging the BPQDs-mediated photothermal effect and the thermoreversible stiffness change of dynamic hydrogel. Additionally, eumenitin and vascular endothelial growth factor were co-loaded in the microspheres and their release behavior can be regulated by the same mechanism. Moreover, effective monitoring of the drug release process can be achieved through visual color variations. The microsphere system has demonstrated desired capabilities of controllable drug release and efficient wound management. These characteristics suggest broad prospects for the proposed composite microspheres in clinical applications. Highlights: 1 Derived from silica photonic crystals, inverse opal microspheres have a regularly connected porous structure and inherit structural color properties. 2 Combined with the stable scaffold and the photothermal phase-transition of the secondary filling material, the inverse opal composite microspheres are endowed with self-healing properties and the ability for controllable drug release. 3 Inverse opal microspheres were significantly treated for diabetic wound, via promoting tissue regeneration, collagen deposition and angiogenesis. Meanwhile, the release of drugs could be monitored by the structural color characteristic.